Haematology and biochemical profiles of endangered local cattle of Andaman and Nicobar Islands - PERUMAL, P; DE, A K; BHATTACHARYA, D; SUNDER, JAI; KUNDU, A (The Indian Journal of Animal Sciences, 2022)
Andaman and Nicobar Islands have two different genetic groups of cattle namely Andaman local cattle and Trinket cattle. Andaman local cattle are distributed in Andaman group of Islands and Campbell Bay of Nicobar group of Islands. Andaman local cattle are non-descriptive and represent an admixture of different Indian breeds that had been brought to these islands in different phases of inhabitation and rehabilitation of migrated people. It is believed that the Andaman local cattle have the inheritance from Red Sindhi, Sahiwal and Hariana. It is unique cattle, well adapted to special type of tropical humid island climatic and environmental condition. The present study was designed to standardise the normal reference haematological and biochemical range for different age groups of Andaman local cattle which were maintained in the South Andaman and North and Middle Andaman district, Andaman and Nicobar Islands, India. In this study, haematological parameters, biochemical indices and antioxidant and oxidative stress profiles were estimated in healthy, normal physiological Andaman local cattle for different age groups. The present study results clearly indicated that the values of haematological, biochemical and antioxidant profiles were under the normal physiological range. These results of this study may serve as the reference values in which alterations due to metabolic, nutrient deficiency, physiological and health status can be compared for diagnostic and therapeutic purposes for Andaman local cattle in Andaman and Nicobar Islands and its neighbouring countries or other parts of the country with similar environmental and climatic conditions.